Arabic Contribution toward Indonesian Vocabularies: Analysis of Q.S. Al-Baqarah - Siti Isnaniah; Tiya Agustina (Islah: Journal of Islamic Literature and History, 2020)
Arabic has a wide contribution toward Indonesian vocabularies, literary and commentary. This writing is aimed to describe the contribution of Arabic toward Indonesian vocabularies in Q.S. Al-Baqarah. The research uses qualitative descriptive method to describe the language forms in surah Al-Baqarah and their influences in Indonesian vocabularies. This research is a library research through content analysis techniques. The primary source of data is verses in Al-Qur’an Surah Al-Baqarah Verse 1 to 286, and the secondary source is Great Indonesian Dictionary Fifth Edition (Kamus Besar Bahasa Indonesia Edisi V/KBBI V). The result of the study shows that there are 52 Indonesian vocabularies come from Arabic; mostly the word “kitab” which appears 19 times, and the least ones are the words mutakin, gaib, rabi, akhir, mukmin, kulub, muslih, maut, lillahi, alim, khalifah, khusyuk, syafaat, furqan, tobat, mati, rahmat, jahiliah, mukmin, magrib, masjid, nikah, duafa, syahid which appear once (1); translation from Arabic to Indonesian in Surah Al-Baqarah is mostly literal translation so it causes a problem in the word “qulub” the plural form of “kalbu” (heart), based on Indonesian grammar, the word is written “kalbu”. The letter “q” which is adapted from Arabic is written as “k” in Indonesian. People who understand Arabic will surely make it a problem because “kalbu” in Arabic (kaf, lam, ba’) means dog. Meanwhile, “qalbu” (qaf, lam, ba’) means heart. For this reason, the writing of the word “qolbu” or “qalbu” is still used by many people or media up to now.